Neuroimaging evaluation of unilateral asymptomatic carotid plaque ulceration: preliminary results of the Carotid Artery Multimodality imaging Prognostic study. (3rd October 2022) - Masini, G; Gargani, L; Napoli, V; Cosottini, M; Chiappino, D; Orlandi, G; D'Amelio, C; Todaro, P; Galeotti, G; Bort, I R; Baldini, M; Aghakhanyan, G; et al.
Abstract: Background: Carotid plaque ulceration has been associated with imaging characteristics of high risk of future events (plaque vulnerability) in patients with a significant degree of stenosis, while little is known about its role in patients with a lesser degree of stenosis and its association with markers of vascular inflammation. Purpose: We evaluated the association between imaging characteristics of plaque vulnerability and vascular inflammation detected by different imaging tests. Methods: One hundred and seven patients with unilateral asymptomatic carotid artery stenosis (40–60% detected by Doppler ultrasound (DUS)), enrolled in the ongoing Carotid Artery Multimodality Prognostic (CAMP) study were prospectively evaluated with computed tomography angiography (CTA), contrast-enhanced magnetic resonance imaging (CEMRA) and, in a subgroup of patients, with 18-F-fluorodeoxyglucose positron emission tomography (PET). Plaque ulceration was detected by CTA. Variables are expressed as median (1st–3rd quartiles) and number (percentages).The Student's t-test or Mann-Whitney and Chi square or Fisher's exact test were used to study associations among variables. Results: An ulcerated plaque was present in 35% patients (n=33) of those undergoing CTA (n=94), while intraplaque hemorrhage and lipid-rich necrotic core were present in 9% and 15% of those undergoing CEMRA. Compared with patients with non-ulcerated plaques, those with an ulcerated plaque had a significant higher degree of stenosis at DUS, a higher target to background ratio (TBR) at 18F-FDG-PET and a higher high-sensitivity cardiac troponin (cTn) T. Conclusions: Plaque ulceration is common and associated with higher degree of stenosis, higher indices of wall inflammation and higher serum markers of myocardial injury. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Regione Toscana